ОПРЕДЕЛЕНИЕ ЭФФЕКТИВНЫХ ПЛОЩАДЕЙ ДЕКАМЕТРОВЫХ РАДИОТЕЛЕСКОПОВ - Рашковский, С. Л.; Шепелев, В. А.; Инютин, Г. А.; Ващишин, Р. В. (Одеські астрономічні публікації, 2011)
A method of a calibration of arrays of the URAN radio telescopes is presented. A number of powerful discrete radio sources located on different declinations were observed with the radio telescopes to obtain dependence of their normalized affective area from a beam orientation. Absolute value of the effective area of each antenna was found by observations of the calibrator 3C405.